Influence of reservoir heterogeneity on immiscible water-alternating-CO2 flooding: A case study - Jia, Peifeng; Cui, Chuanzhi; Wu, Zhongwei; Yan, Dawei (Energy Geoscience, 2024)
Currently, limited studies of immiscible water-alternating-CO2 (imWACO2) flooding focus on the impact of reservoir heterogeneity on reservoir development outcomes. Given this, using the heterogeneous reservoirs in the Gao 89-1 block as a case study, this study conducted slab core flooding experiments and numerical simulations to assess the impact of reservoir heterogeneity on imWACO2 flooding efficiency. It can be concluded that imWACO2 flooding can enhance the sweep volume and oil recovery compared to continuous CO2 flooding. As the permeability difference increases, the difference in the swept volume between zones/layers with relatively high and low permeability increases. To optimize the exploitation of reservoirs in the Gao 89-1 block, the optimal timing and CO2 injection rate for imWACO2 flooding are determined at water cut of 40% and 10000 m³/d, respectively. A short injection-production semi-period, combined with multiple cycles of water and CO2 injection alternations, is beneficial for enhanced oil recovery from imWACO2 flooding. [Display omitted] •The imWACO2 flooding can extend the sweeping volume and improve the recovery.•The imWACO2 can eliminate the adverse influence of the heterogeneity to a certain extent.•The optimal timing of imWACO2 and injection CO2 velocity are obtained for target reservoirs.